Development and Evaluation of a Mobile Application as an e-Learning Tool for Technical Wine Assessment. - Wilkinson, Kerry; Able, Amanda J. (Office for Learning and Teaching, 2016)
Objective training in technical wine assessment is a critical component of wine education. A prototype iPad application (App) was developed to enable students to characterise the appearance, aroma, taste and mouthfeel (i.e. sensory attributes) of wine, to generate detailed tasting notes according to industry best practice, within a searchable, downloadable archive. The project evaluated the App's impact on student learning and assessment, for example, by incorporating an online database to capture students' tasting experience (i.e. the range and frequency of tastings), thereby enabling convenient assessment of students' sensory skills and experience throughout their degrees. Additionally, the project team workshopped their experience in App design and development with others interested in developing Apps as e-learning tools for higher education. In this way, the project represents a case study in the innovative use of technology in learning and teaching.